Anti-Inflammatory Effect of the Epigallocatechin Gallate Following Spinal Cord Trauma in Rat - Khalatbary, Ali Reza (Pasteur Institute of Iran, 2011)
Background: Spinal cord injury (SCI) stimulates an inflammatory reaction that causes substantial secondary damage inside the injured spinal tissue. The purpose of this study was to determine the anti-inflammatory effects of epigallocatechin gallate (EGCG) on traumatized spinal cord. Methods: Rats were randomly divided into four groups of 12 rats each as follow: sham-operated group, trauma group, and EGCG-treatment groups (50 mg/kg, i.p., immediately and 1 hour after SCI). Spinal cord samples were taken 24 hours after injury and studied for determination of myeloperoxidase (MPO) activity, histopathological assessment and immunohistochemistry of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), Nitrotyrosine, inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and poly(ADP-ribose) polymerase (PARP). Results: The results showed that MPO activity was significantly decreased in EGCG-treatment groups. Attenuated TNF-α, IL-1β, Nitrotyrosine, iNOS, COX-2, and PARP expression could be detected in the EGCG treated rats. Also, EGCG attenuated myelin degradation. Conclusion: On the basis of these findings, we propose that EGCG may be effective in protecting rat spinal cord from secondary damage by modulating the inflammatory reactions.